Experimental and Theoretical Investigations of Cordia Obliqua Leaves Extract as an Environmentally Benign Inhibitor for Mild Steel Corrosion in a 1 M HCl Solution - Minagalavar,Ragini L. (2024)
Abstract MS surface deterioration is one of the most challenging problems, since it can be exacerbated by several industrial processes, such as descaling and pickling. In the proposed investigation, chemical and electrochemical techniques determined COLE IE(%) on MS corrosion in a 1 M HCl medium. COLE contains many Pc responsible for an excellent IE(%), since it forms a coating that adsorbs onto the metal surface and shields it from corrosion. Tafel polarization curves outcomes demonstrated that COLE is a mixed kind of CI. According to EIS measurements, Rct rose as Ct of COLE was increased. The relationship between T and MS corrosion behaviour in 1 M HCl with COLE addition was investigated from 300 to 320±1 K. G, which was determined from Langmuir’s isotherm model, revealed that COLE molecules predominantly blocked HCl attack by mixed physisorption and chemisorption mechanisms. Surface morphology studies validated electrochemical and chemical findings by FT-IR, SEM and WCA techniques. Furthermore, DFT computations demonstrated COLE effective interfacial adsorption onto the MS surface.